Konsep Kampung Vertikal Pada Penataan Kawasan Rawan Banjir dengan Konsep Kampung Vertikal di Kampung Melayu Jakarta - Andrea Gina Karima; Ari Widyati Purwantiasning; Lutfi Prayogi (Arsitektur UMJ, 2018)
Kampung Melayu is one of the flood-prone areas in East Jakarta. An annual flood which occurs in this village often immersed residents up two meters tall. Slum condition of the village as the effect of adjacent location with the Ciliwung River and the post-flood condition caused a poor environment for the community. Therefore, the arrangement of flood-prone areas in Kampung Melayu aims to improve the quality of life for the community and environment which is in accordance with the regulations of the Provincial Government of DKI Jakarta, accommodates the needs of facilities and infrastructure of the settlement, and creates the image of urban kampong culture in Kampung Melayu. It is necessary to arrange flood-prone areas with the concept of vertical kampong in Kampung Melayu. The method of preparing the concept used is theoretical basis and field observation, data processing, and data analysis to compose the concept of planning and design “Penataan Kawasan Rawan Banjir dengan Konsep Kampung Vertikal di Kampung Melayu”.